Case reports of middle ear muscular spasms presenting as tinnitus - Ali Hanafiah, Nurlin; Jamaluddin, Saiful Adli; Zamzuri, Nur Airin Zulaikha; Al-Hadeethi, Yahia F. Hussein; Wan Mohamad, Wan Najibah (IIUM Press, 2025)
Background: Middle ear myoclonus (MEM) is an uncommon disorder characterised by involuntary spasms of the middle ear muscles, often manifesting as objective or pulsatile tinnitus. There are currently no standardised diagnosis or treatment methods, which may result in a chronic impairment in patients' quality of life despite intervention. This study seeks to characterize cases of MEM presented at a tertiary care clinic, with a focus on the diagnostic and management approaches employed. Methods: Two clinical cases of MEM were identified from the tinnitus clinic at the Department of Otorhinolaryngology - Head and Neck Surgery, SASMEC @IIUM. Cases were included if they involved patients who had been diagnosed with MEM-induced tinnitus and provided information on diagnostic processes and methods of treatment. Results: Two cases of MEM with either objective or subjective tinnitus were presented. Otoscopy and tympanometry were normal across cases, but differences emerged in the use of otoacoustic emissions (OAE), stapedial reflex testing, and pure tone audiometry for assessment. Some cases also utilized imaging to exclude other possible causes. Management strategies ranged from reassurance and pharmacological therapy to surgical tendon sectioning. The SASMEC@IIUM cases favoured conservative approaches: mainly reassurance, counselling, and ongoing monitoring, compared to the more invasive interventions reported in other institutions. Conclusion: The observed variability in the diagnosis and management of MEM underscores the lack of standardized clinical guidelines. To facilitate the development of evidencebased protocols, further research involving larger sample sizes and appropriately matched control groups is essential. Such efforts are likely to enhance diagnostic consistency and improve treatment outcomes for patients with MEM-induced tinnitus.